2014
DOI: 10.1016/j.virol.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the human rhinovirus C capsid suggests a novel topography with insights on receptor preference and immunogenicity

Abstract: Features of human rhinovirus (RV)-C virions that allow them to use novel cell receptors and evade immune responses are unknown. Unlike the RV-A+B, these isolates cannot be propagated in typical culture systems or grown for structure studies. Comparative sequencing, I-TASSER, MODELLER, ROBETTA, and refined alignment techniques led to a structural approximation for C15 virions, based on the extensive, resolved RV-A+B datasets. The model predicts all RV-C VP1 proteins are shorter by 21 residues relative to the RV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Of the 4 immunodominant RV-C regions identified in this study, three (C1, C3, and C4) are located in regions presenting species-specific amino acid substitution and one (C2) is located in the VP1 region that had major species C-specific amino acid deletions. Our findings on RV-C-specific T-cell epitopes provide experimental evidence that corroborates the predictions made on the basis of bioinformatics tools (29), which suggested that RV-Cs have new, unique epitopes that are well conserved within species C (29).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Of the 4 immunodominant RV-C regions identified in this study, three (C1, C3, and C4) are located in regions presenting species-specific amino acid substitution and one (C2) is located in the VP1 region that had major species C-specific amino acid deletions. Our findings on RV-C-specific T-cell epitopes provide experimental evidence that corroborates the predictions made on the basis of bioinformatics tools (29), which suggested that RV-Cs have new, unique epitopes that are well conserved within species C (29).…”
Section: Discussionsupporting
confidence: 87%
“…4, red boxed regions). Furthermore, species C presents major amino acid deletions, especially in the center of VP1, which shortened the protein by 21 residues compared to VP1 of species A (29). Of the 4 immunodominant RV-C regions identified in this study, three (C1, C3, and C4) are located in regions presenting species-specific amino acid substitution and one (C2) is located in the VP1 region that had major species C-specific amino acid deletions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…To test the feasibility of virus-receptor interactions, we docked the CDHR3 domains 1, 2, and 3 to a two-protomer model of RV-C15 capsid (23). Preliminary mutagenesis experiments suggested that Asn 186 , but not Trp 86 , was participating in virus binding; therefore, both queried algorithms [Gramm-X (24) and HAD-DOCK (25)] were given only two constraints: (i) CDHR3 Asn 186 should be at or near the interface and (ii) the solvent exposed (outer) surface of the capsid proteins should be involved.…”
Section: Development and Characterization Of Transduced Hela Cell Linementioning
confidence: 99%
“…The RV-C as a species conserves <75% capsid protein identity, but the RV-C15 structure model predicts a single shared receptor (23). The modeled CHDR3 footprint covers nearly every surface residue of RV-C15 that is conserved within the species (Fig.…”
Section: Development and Characterization Of Transduced Hela Cell Linementioning
confidence: 99%